The advantages of SAP system functions to the MSGP system for the finance department – a case study on HeiTech Padu Berhad / Wan Marjan Wan Mhd Kamal - Wan Mhd Kamal, Wan Marjan (2011)
HeiTech Padu Bhd. is a public listed company as the Malaysia’s leading ICT Solutions. This research is to study and identify what is the system used in the company and what it is all about. This covers the process flow and advantages of this new system to the company instead of the previous one they used. Thus, finance department is chosen as the area of this study and Account Receivable(AR) unit is the scope that I would like to cover here. Therefore, I will explain and discuss the about the system which is the SAP in terms of its functions, advantages, and how it works and benefits the company compared to the previous system which was the MSGP. Overall, this study will focus more on the SAP system which is also becoming the issue of why they have changed from the old system used. Data and information had been collected from the internet, journals, articles as well as from interviewing the executives in HeiTech Padu Bhd. The result indicates that, the used of the new system contribute to the reasons of why they need to changed from the previous system formerly.